O setor de seguros e o marketing de relacionamento - Castro, Alexsandre de (2004)
The great growth of the market insurer in Brazil brought, to the long one of the last ones, difficulties for the companies to become related adequately with its customers (correctors and insured), compelling them to rethink it its businesses. In this context, the behavior of the consumer of the market automobile insurance assumes special connotation and starts to be obligator question in the search of the competitive advantage. Thus, the general objective of the present study is to establish procedures between the corrector, the insured and the insuring one, with a plan of action of fidelização to maximize resulted for the companies, from strategies of relationship marketing, based in the triad customer, insuring corrector ando For in such a way, it is used of a theoretical and empirical survey of the reality of the sector of automobile insurances, refined in the current period of training, and presents concepts and tools of marketing of relationship that adapted could lead to the increase of the values collected for the insuring ones, with conquest of new customers and retention of the current ones. The results indicate that it has innumerable of possible applications of relationship marketing in the insurances automobile segment, as suggests the study of case of the Niterói branch office of the searched organization, capable to make with that the companies of the sector develop its prescription potential and maximize its relationship with the correctors and the final consumers